Cutis Marmorata Telangiectatica Congenita in a Preterm Female Newborn: Case Report and Review of the Literature - C. De Maio; G. Pomero; A. Delogu; E. Briatore; M. Bertero; P. Gancia (PAGEPress Publications, 2014)
Cutis Marmorata Telangiectatica Congenita (CMTC) is a rare, sporadic condition usually present at birth characterized by localized or generalized persistent cutis marmorata, telangiectasia and phlebectasia. We report a preterm female newborn, the third child of non-related caucasian parents, with CMTC at birth who showed typical cutaneous features and monolateral congenital glaucoma. The pathogenesis of this disorder is unknown and the cause is probably multifactorial. Teratogens and autosomal dominant mode of inheritance with incomplete penetrance have been considered as etiological factors. Prognosis, in uncomplicated cases, is good.